HUBUNGAN ANTARA SERVICE QUALITY DENGAN KEPUASAN KONSUMEN DI RESTORAN X - Widodo, Purwanto (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
This research intent to know quality influence service quality to consumer satisfaction at restaurant X. Variable quality services to utilize Parasuraman's variable,Zeithaml, berry (1985) one that consisting: which is; Tangibles, Empathy, Reliability, Responsiveness and Assurance. Sample that takes to be done by purposive is sampling . To determine sample measure utilize formula from Walpole (1998). With trusty zoom 95 percents, error sampling 10 percents and is assumed that population so heterogeneous therefore sample amount that is taken equals 96 respondents. Result observationaling to point out that variable together ala Tangible, Reliability, Responsiveness, Assurance and Emphaty having for to Customer satisfaction. Meanwhile partial's ala, Tangible'svariable and Emphaty what does positive ascendant and signifikan to Customer satisfaction. Determinant coefficient as big as 68,5 percents